Retrospective Outcome Analysis of Allogenic Bone Graft - Maheshwari, Vikas; Dhingra, Mohit; Sharma, Divyansh; Gowda, Aditya K. S.; Kurmi, Arun; Das, Surabhi (South Asian Journal of Cancer, 2023)
Bone bank has become an essential requirement for centers that perform tumor and reconstructive surgeries. It provides allogenic bone procured from cadavers as well as live donors in the form of surgical residues. Thus, we conducted a retrospective observational study on recipients who underwent various reconstructive procedures using fresh frozen allograft obtsined from the live donors through surgical residues in a newly established bone bank. The outcomes of cases operated where allogenic bone grafts were used between January 2018 and November 2020 were analyzed in terms of infection and time taken for the grafts to incorporate, allowing weight-bearing in the lower limbs. A total of 223 grafts were obtained as surgical residues from replacement surgeries and traumatic amputations performed on non-salvageable limbs. Out of these, 70 grafts were transplanted into eligible recipients, who were followed up for at least one year. Among the 70 recipients, 15 were lost to follow-up. The outcome data of the remaining 55 recipients was tabulated, including infections (early, delayed and late) and the achievement of weight-bearing milestones when transplanted in lower limbs. Out of the 55 cases, allografts were used alone in 20 cases, while in 35 cases, they were augmented by implants or cement. Two cases (3.6%) experienced acute infections, and another two cases (3.6%) had chronic infection. The mean time for weight-bearing was found to be 7 months when used alone and 3.5 months when augmented with cement or an implant. Additionally, five patients did not show complete integration of the graft. The results of using allogenic bone graft are quite encouraging, suggesting their potential as biological adjuvants in reconstructive surgeries.
Keywords: allograft; bone bank; outcome analysis; infection; graft incorporation